2023
DOI: 10.3390/brainsci13040542
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Monocytes-Macrophages in Immune Microenvironment of Glioblastoma for the Design of Novel Therapeutic Strategies

Abstract: Gliomas are primary malignant brain tumors. These tumors seem to be more and more frequent, not only because of a true increase in their incidence, but also due to the increase in life expectancy of the general population. Among gliomas, malignant gliomas and more specifically glioblastomas (GBM) are a challenge in their diagnosis and treatment. There are few effective therapies for these tumors, and patients with GBM fare poorly, even after aggressive surgery, chemotherapy, and radiation. Over the last decade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 175 publications
0
6
0
Order By: Relevance
“…On the contrary, M2 has an anti-inflammatory and tumor progression promoter phenotype, which produces IL-10, VEGF and causes immunosuppression to promote tumor development. [ 44 ] Studies have shown that glioblastoma with a high proportion of monocyte has mesenchymal characteristics, increased angiogenesis, and poor prognosis. [ 45 ] Other studies have also shown that high expression of macrophage related genes predicts poor prognosis in glioma patients with mesenchymal subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, M2 has an anti-inflammatory and tumor progression promoter phenotype, which produces IL-10, VEGF and causes immunosuppression to promote tumor development. [ 44 ] Studies have shown that glioblastoma with a high proportion of monocyte has mesenchymal characteristics, increased angiogenesis, and poor prognosis. [ 45 ] Other studies have also shown that high expression of macrophage related genes predicts poor prognosis in glioma patients with mesenchymal subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, interactions between the immune components of TME and GBM cells enhance the adaptive fitness of tumor cells within the hypoxic niche through MES reprogramming ( Figure 2 ). Such interactions can provide valuable insights into the complex cellular and molecular interplay with the TME and may also yield innovative therapeutic targets [ 139 , 140 ].…”
Section: Mes Reprogrammingmentioning
confidence: 99%
“…Macrophages in gliomas were differentiated from VEGF producing monocytes. The number of macrophages was positively correlated with VEGF expression ( 50 ). Meanwhile, macrophages upregulate VEGFR1 expression and promote formation of GAMs ( 51 ).…”
Section: Vegfmentioning
confidence: 99%